Effects of dry needling to the symptomatic versus control shoulder in patients with unilateral subacromial pain syndrome. (December 2016) - Koppenhaver, Shane; Embry, Robin; Ciccarello, John; Waltrip, Justin; Pike, Rachel; Walker, Michael; Fernández-de-las-Peñas, Cesar; Croy, Theodore; Flynn, Timothy
Abstract: Background: Initial reports suggest that treating myofascial trigger points in the infraspinatus with dry needling may be effective in treating patients with shoulder pain. However, to date, high quality clinical trials and thorough knowledge of the physiologic mechanisms involved is lacking. Objectives: To examine the effect of dry needling to the infraspinatus muscle on muscle function, nociceptive sensitivity, and shoulder range of motion (ROM) in the symptomatic and asymptomatic shoulders of individuals with unilateral subacromial pain syndrome. Design: Within-subjects controlled trial. Methods: Fifty-seven volunteers with unilateral subacromial pain syndrome underwent one session of dry needling to bilateral infraspinatus muscles. Outcome assessments, including ultrasonic measures of infraspinatus muscle thickness, pressure algometry, shoulder internal rotation and horizontal adduction ROM, and questionnaires regarding pain and related disability were taken at baseline, immediately after dry needling, and 3–4 days later. Results: Participants experienced statistically significant and clinically relevant changes in all self-report measures. Pressure pain threshold and ROM significantly increased 3–4 days, but not immediately after dry needling only in the symptomatic shoulder [Pressure pain threshold: 5.1 (2.2, 8.0) N/cm 2, internal rotation ROM: 9.6 (5.0, 14.1) degrees, horizontal adduction ROM: 5.9 (2.5, 9.4) degrees]. No significant changes occurred in resting or contracted infraspinatus muscle thickness in either shoulder. Conclusions: This study found changes in shoulder ROM and pain sensitivity, but not in muscle function, after dry needling to the infraspinatus muscle in participants with unilateral subacromial pain syndrome. These changes generally occurred 3–4 days after dry needling and only in the symptomatic shoulders. Highlights: Dry needling may change pain sensitivity and ROM in patients with shoulder pain. These changes appear to relate to symptomatic side impairments and take several days to occur. Dry needling may not change infraspinatus muscle function. Or, changes in muscle function might be specific to treated regions within a muscle.